Flint artefacts from the Wielbark culture cemetery at Weklice, Site 7, Elbląg county - Magdalena Natuniewicz-Sekuła; Dagmara H. Werra (Journal of Lithic Studies, 2016)
In the Bronze Age flint was still being used throughout Europe. In the early periods of that age flint continued to play an important role in the economy in many areas, as evidenced by the numerous flint mines in use at the time as well as flint tools. In the Late Bronze and Early Iron Ages, flint still had an important place in the economies of communities living in East Central Europe. At the same time, analysis of late flint industries suggests that some of those had no utilitarian significance. The presence of flint, especially in inhumation graves from the cemetery at Weklice (used by communities of the Wielbark culture during the Roman Period) potentially adds to the debate about its significance. The cemetery at Weklice is the one of the best-known sites from the Roman Period in Poland. The graves are mostly equipped with local finds of metals: gold, silver, copper alloys, iron and amber as well as Roman imports (glass beads, vessels: glass, copper alloys). The collections comprise over of 4000 finds, however this number may change, as excavations in 2012 and 2013 revealed 22 flint artefacts. The presence of flint materials in a Roman Period cemetery admits several possible interpretations: 1) Those may be remnants of older settlements, with graves being dug into older strata and thus some of the specimens of flint could be in their secondary filling on the site; 2) Those may be remains of flint knapping activity by the Wielbark culture community; 3) Those may have been placed in the graves deliberately by the Wielbark culture community as an instance of an older custom involving the placing of flint in graves.